The Implementation of Literacy Strategies in Teaching English by the English Teacher at MAN Insan Cindekia Padang Pariaman - Khairuddiniyah, Khairuddiniyah (English Education: Jurnal Tadris Bahasa Inggris, 2017)
The global life requires the necessity to read well enough to be able to function sufficiently in this changing global population. The students have to be able to access to reading for a particular purpose and to literacy. For that reason, it is important to develop EFL teaching system appropriately to develop students’ literacy competency. Therefore, this paper explores a study of the implementing literacy strategies by English teacher at MAN Islam Cendekia Padang pariaman, Sumbar, Indonesia. Through classroom observation and interview to the process of implementing literacy strategies in the classroom by the English teacher, results revealed that literacy strategies by EFL teacher in MAN IC PAPAR has no exposure to the specific how to implement literacy strategies in teaching. This will lead to the need for the establishment of standard in implementing literacy strategies to ensure the achievement of goal of teaching English. This paper suggests that related to the aspect to be covered in standards, namely (1) promoting literacy as well content learning (2) the text, and (3) learning situation. Another suggestion should involves as many parties concerned as possible, including, government, students’ parents, and school environment.